Garlic cultivation : A profitable enterprise for farmers in Kiphire district - Ezung, N Khumdemo; Jamir, Temjenna; Sangtam, Litekhing S (Indian Farming, 2025)
Kiphire district, primarily known for maize and rice cultivation, has seen a shift towards garlic farming, led by progressive farmers like Shri Setoli Sangtam. After training at VPKAS (Almora), Shri Setoli adopted the VL Lasun 2 garlic variety in 2020, supported by two Jalkund water harvesting structures to address seasonal irrigation challenges. This innovative approach resulted in significant profits, with net earnings rising from ` 37,800 in 2020 to 110,000 in 2022. The high demand for his garlic in the local market underscores the crop’s potential, promoting sustainable agricultural practices and encouraging other farmers in the region to diversify their crops.